2014
DOI: 10.1039/c4md00115j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of a series of quinolinyl trans-cyanostilbene analogs as anticancer agents

Abstract: 2-Quinolyl- and 3-quinolyl-cyanocombretastatin analogs exhibit potent growth inhibition against a panel of 60 human cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…According to previous literature, base-catalyzed condensation of aryl/heteroaryl aldehydes with aryl/heteroaryl acetonitriles leads exclusively to the formation of the ( Z )-isomer. 14a–14c We confirmed the ( Z ) configuration of analogues 7a – 7g by carrying out carbon-proton coupling experiments to determine the magnitude of the coupling constant ( J CH ) of the CN carbon doublet that results from coupling with the adjacent olefinic proton. 14b …”
Section: Chemistrymentioning
confidence: 55%
See 1 more Smart Citation
“…According to previous literature, base-catalyzed condensation of aryl/heteroaryl aldehydes with aryl/heteroaryl acetonitriles leads exclusively to the formation of the ( Z )-isomer. 14a–14c We confirmed the ( Z ) configuration of analogues 7a – 7g by carrying out carbon-proton coupling experiments to determine the magnitude of the coupling constant ( J CH ) of the CN carbon doublet that results from coupling with the adjacent olefinic proton. 14b …”
Section: Chemistrymentioning
confidence: 55%
“…1; structure D ); these compounds are potent anti-cancer agents which are not substrates for cellular P-glycoprotein. 14c In this respect, Ohsumi et al have reported that ( E )-substituted diarylacrylonitrile analogues structurally related to the combretastatins (Fig. 1; structure E ) are also effective anti-cancer agents against murine solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported on the synthesis and anti-cancer activities of a series of ( Z )-quinolinylcyano- ( V ) and ( E)- and ( Z ) - benzothiophene cyanocombretastatin analogues (Fig. 1, VI ) [11, 12], and have determined that such analogues (e.g. compound 29 , Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on combretastatin analogues have shown that replacement of the 3-hydroxy-4-methoxyphenyl moiety of CA-4 with heterocyclic groups such as quinoline, quinazoline and benzothiophene results in improved anti-cancer activity [11, 12, 33]. In the present work, we have synthesized a variety of heterocyclic ( Z )-cyanocombretastatin analogues that incorporate 2- and 3-indolyl, 2- and 3-benzofuranyl, 2-benzothiophenyl, and 2-benzothiazolyl moieties as replacements for the 3-fluoro-4-methoxyphenyl group in ( Z )-cyano CA-4 [9] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…17 Also, we have recently described the synthesis and potent anti-cancer activity of some cis - and trans -cyanostilbene analogs in which one of the phenyl moieties has been replaced with a heteroaromatic moiety such as benzothiophene 19 and quinoline. 20 …”
mentioning
confidence: 99%